Assessing the School Environment: A Study of Physical Condition and Science Teachers’ Perception in Multan - Gul, Matin; Raza, Mohsin (JSE, 2025)
The study evaluates the physical school environment of public secondary schools in the District Multan, Pakistan, against World Health Organization (WHO) guidelines by the perception of science teachers. The science teachers are chosen due to their qualifications in chemistry and biology, and their understanding of chemical and biological reaction of physical school environment. Recognizing by science teacher, that a school's physical condition is a critical determinant of student health, enrollment, and academic performance, this research assesses ten basic indicators, including waters’ quality, sanitation services, good hygiene practices, waste disposal, Conditions of building, and safety. Employing a mixed-methods convergent parallel design, data were collected from 158 schools via questionnaires for school heads and science teachers, supplemented by direct diary observations. While indicators like School security and waste disposal were relatively better, none met the international standard. The analysis also uncovered stark disparities, with urban schools demonstrating significantly better conditions than rural schools, and notable variations across different tehsils. The study also revealed that science teachers as respondents played a vital role as a critically, scientifically and significantly in study keeping in view their science subject knowledge. The study concludes that despite some progress, the physical infrastructure of schools in Multan falls considerably short of WHO standards, potentially hindering educational outcomes. It recommends the formal adoption of WHO guidelines, conducting comprehensive facility surveys, and implementing targeted programs to address the identified gaps, with a specific focus on improving water safety and sanitation, particularly in rural and female schools.